Determinants of financial well-being among young workers: an empirical investigation / Nor Shahrina Mohd Rafien and Shafinar Ismail - Mohd Rafien, Shahrina; Ismail, Shafinar (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
Financial well-being is one of the elements of well-being where an individual can control the financial matters of current life and future life as well, without feeling worries about his or her financial situation and it is vital to get a better quality of life. Therefore, this study aims to analyse the factors that influence financial well-being among young workers. Three variables are tested for this study namely, financial knowledge, financial capability and parent influence. The sample for this study consisted of 226young workers aged between 18-30 years who participated in the survey using purposive sampling technique among working persons in all the states in Peninsular Malaysia. The data was collected via online form. Multiple regression analysis was employed to analyse the data gathered. The findings revealed that there was a significant relationship between financial capability with financial well-being among young workers. However, there was an insignificant effect between financial knowledge and parent influence towards well-being among young workers. The results could be used as a guide to related government agencies, financial institutions, and the individual as well in understanding the importance of financial well-being to curb from facing financial problems and to sustain the quality of life. A good financial well-being program such as by conducting a seminar may help the young workers in understanding their level of financial well-being.